Views of teenagers on termination of pregnancy at Muyexe high school in Mopani District, Limpopo Province, South Africa - Nditsheni J. Ramakuela; Tsakani R. Lebese; Sonto M. Maputle; Lindiwe Mulaudzi (AOSIS, 2016)
Background: Teenage pregnancy is a global social health concern especially because of the HIV and AIDS pandemic, sexually transmitted infections, high rate of termination of pregnancy (TOP), adolescents' parenthood and decreased level of contraceptives. Aim: To explore the views of teenagers on the TOP at Muyexe high school in a rural village of Mopani District, Limpopo Province. Setting: Muyexe high school in a rural village of Mopani District, Limpopo Province, in South Africa. Methodology: A qualitative method using explorative and descriptive designs was used to find in-depth description and understanding of teenagers' views on TOP. The target population was girls aged 15-19 years at Muyexe high school in Mopani District. Non-probability, convenient sampling was used to select high school teenage girls who had undergone TOP for the study. Data were collected using individual self-report technique (interview). Tesch's eight steps of qualitative data analysis were used. Measures to ensure trustworthiness and ethical considerations were observed. Results: Two major themes were revealed: (1) Views of teenagers regarding TOP (poverty, relationship problems and single parenthood, negative impact on the teen's life while attending school) and (2) teenager's fears regarding pregnancy (stigma, fear of parents and friends, rape and incest and fear of giving birth). Conclusion: Majority of participants had knowledge about TOP; some had experiences about TOP while others held inadequate knowledge. Recommendations were based on the findings by teaching dangers of TOP and various contraceptive methods to prevent unwanted pregnancies and TOP. Keywords: Views, teenagers and termination of pregnancy